2022
DOI: 10.3389/fcvm.2022.814505
|View full text |Cite
|
Sign up to set email alerts
|

Regional Fat Distributions Are Associated With Subclinical Right Ventricular Dysfunction in Adults With Uncomplicated Obesity

Abstract: ObjectiveObesity is a prominent public health problem that has increased cardiovascular mortality risks. However, the specific effects of obesity, independent of comorbidities, on cardiac structure and function have not been well clarified, especially those effects on the right ventricle (RV). Cardiovascular magnetic resonance (CMR) tissue tracking can assess detailed RV mechanical features. This study aimed to evaluate RV strain using CMR in uncomplicated obese adults and assess its association with fat distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Higher QI at maximum exercise in controls was associated with a further decrease in TAPSE/sPAP ratio. The changes in TAPSE/sPAP ratio with exercise were correlated to the android fat mass which confirms that central obesity has a negative effect on RV function (8).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Higher QI at maximum exercise in controls was associated with a further decrease in TAPSE/sPAP ratio. The changes in TAPSE/sPAP ratio with exercise were correlated to the android fat mass which confirms that central obesity has a negative effect on RV function (8).…”
Section: Discussionsupporting
confidence: 57%
“…Previous echocardiographic and magnetic resonance imaging studies have shown that obesity is associated with increased RV dimensions and hypertrophy, and depressed indices of systolic function (6)(7)(8). This was confirmed by an invasive study, which reported on a decreased RV/PA coupling assessed by gold standard Ees/Ea that was correlated to a decreased exercise capacity and decreased PA compliance (9).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We know that fat in obese people is often centrally accumulated, which is reflected in visceral fat, abdominal subcutaneous fat, hip fat and other regional fat. Previous studies have shown that the excessive distribution of Android fat and trunk fat may have a deleterious impact on subclinical right ventricular function, while the peripheral fat distribution may have a positive impact ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical practice, longitudinal strain (deformation in the base-apex direction) is useful for evaluating left ventricle contractile function [2]. Some cardiometabolic conditions like type 2 Diabetes Mellitus (t2DM), insulin resistance or obesity may induce cardiac myofibrillary dysfunction [3][4][5].…”
Section: Introductionmentioning
confidence: 99%